2018
DOI: 10.14419/ijet.v7i3.12.16024
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Mechanical and Durability Properties of Soil Building Blocks Reinforced with Synthetic Fibre

Abstract: Earth construction is the most economic way to solve housing problems, particularly in case of low cost building, with the limitation of resources. The simplicity in production of earth blocks justifies by the availability of soil as raw material and by the less energy in production. Generally, fibre inclusion increases the strength and performance of the earth blocks. Synthetic fibre such as AR glass fibre, polypropylene fibre were used and investigated experimentally with different percentages of fibre 0.25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…(a) (b) The same trend noticed in this study was outlined in [59]. The use of natural sugarcane bagasse in [60] revealed a rise in shrinkage with sugarcane bagasse dosage up to 5 % vol fraction.…”
Section: Linear Volumetric Shrinkage and Weight Losssupporting
confidence: 86%
“…(a) (b) The same trend noticed in this study was outlined in [59]. The use of natural sugarcane bagasse in [60] revealed a rise in shrinkage with sugarcane bagasse dosage up to 5 % vol fraction.…”
Section: Linear Volumetric Shrinkage and Weight Losssupporting
confidence: 86%
“…Jalaei & Jrade [15] reported similar results on compressed stabilized earth bricks reinforced with polypropylene fibre and concluded that the inclusion of fibre prevents catastrophic failure and improves the post-initial crack performance of the sample. Results found here (Figure 8) are at variance with Selsiadevi & Ramani [16] ones. They reported that the tensile strength of polypropylene fibre (12 mm length and 0.15 mm diameter) reinforced laterite soil bricks increases with the increase in fibre content, and the investigation was conducted up to 1% fibre content by the dry weight of the soil.…”
Section: Splitting Tensile Strengthsupporting
confidence: 54%
“…The increase in compressive strength of polypropylene fibre reinforced concrete specimens may be attributed to the polypropylene fibre acting as a bonding material between the surrounding particles or to the geometric shape and interface of the fibre [15]. Selsiadevi & Ramani Sujatha [16] attributed the increase in strength to the frictional resistance developed between the fibre and the soil matrix. It is also important to note that the failure mode in every test with monofilament polypropylene fibre was ductile, while with unreinforced soil, the failure was brittle.…”
Section: Compression Strength Of the Bricksmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the presence of a high proportion of EPS beads increases the number of pores and voids in the bricks [23], leading to increased water migration into the CEB. Indeed, several studies have shown that the incorporation of plastic aggregates in bricks leads to an increase in the water absorption rate of the bricks [23,[34][35][36][37]. This increase would be due to the inclusion of heterogeneities by the plastic, which would probably make the materials more porous.…”
Section: Water Absorptionmentioning
confidence: 99%